Answer:
4. 3. 10
5. 1102.31
6. 17.37
Step-by-step explanation:
Answer:
(x + 1) (3 x^2 + 1)
Step-by-step explanation:
Factor the following:
3 x^3 + 3 x^2 + x + 1
Factor terms by grouping. 3 x^3 + 3 x^2 + x + 1 = (3 x^3 + 3 x^2) + (x + 1) = 3 x^2 (x + 1) + (x + 1):
3 x^2 (x + 1) + (x + 1)
Factor x + 1 from 3 x^2 (x + 1) + (x + 1):
Answer: (x + 1) (3 x^2 + 1)
Answer: (C
Step-by-step explanation: To evaluate this, solve by raising 7 to the power of 3.
7 x 7 x 7
7 x 7 = 49 x 7 = 343
Therefore, the answer is C.
The answer is B. Thank you